The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/jn/nxaa002
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Increases Endothelial Function in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background The endothelium plays a key role in the maintenance of vascular health and represents a potential physiological target for dietary and other lifestyle interventions designed to reduce the risk of cardiovascular diseases (CVD) including stroke or coronary heart disease. Objective To conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) investigating the effects of the Mediterranean die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 54 publications
1
36
1
1
Order By: Relevance
“…Likewise, a 12-week MedDiet intervention, with and without exercise, significantly increased endothelial progenitor cells [139]. These effects may contribute towards the improved endothelial function reported with MedDiet interventions [140] Olive oil enhances osteoblastogenesis and adipogenesis in mesenchymal stem cells, reducing the risk of osteoporosis in rats and humans [141]. Additionally, in a sub-study of the PREDIMED trial, which involved 127 older participants (mean age 68 years), intervention with a MedDiet enriched with extra virgin olive oil for two years significantly increased serum osteocalcin, suggesting protective effects on bone [142].…”
Section: Stem Cell Exhaustionmentioning
confidence: 82%
“…Likewise, a 12-week MedDiet intervention, with and without exercise, significantly increased endothelial progenitor cells [139]. These effects may contribute towards the improved endothelial function reported with MedDiet interventions [140] Olive oil enhances osteoblastogenesis and adipogenesis in mesenchymal stem cells, reducing the risk of osteoporosis in rats and humans [141]. Additionally, in a sub-study of the PREDIMED trial, which involved 127 older participants (mean age 68 years), intervention with a MedDiet enriched with extra virgin olive oil for two years significantly increased serum osteocalcin, suggesting protective effects on bone [142].…”
Section: Stem Cell Exhaustionmentioning
confidence: 82%
“…Dyslipidemia is one of the prominent risk factors of the progression of atherosclerosis, which is an underlying cause of CVD [16]. Emerging evidence revealed that the MD diet has a protective effect against dyslipidemia and CVD [4,[31][32][33]. Although the precise mechanism between the MD and lipid metabolism has not yet been elucidated, many interrelated and overlapping components of the MD exert lipid-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these indicate that rather than being harmful, dietary NO 3 − intake is inversely associated with cardiovascular disease risk [102,194] and certain cancers [117]. Furthermore, diets and dietary patterns high in fruits and vegetables are linked to greater longevity [195,196], protection against type 2 diabetes [197] and chronic obstructive pulmonary disease [198], and improved cardiovascular [92,199,200] and cognitive health [201,202]. This suggests that higher intake of dietary NO 3 − , at least through plants, is more likely to be associated with health benefits than adverse effects.…”
Section: Nomentioning
confidence: 99%